The effect of dietary level of Vitamin E on Humoral Response Quail (Cortunix cortunix Japonica) against newcastle disease vaccination - Mohamad Asrol, Kalam (2015)
A total of 120 one-day-old quail (Cortunix cortunix japonica) were used in this study. Quails are fed diets supplemented with different level of vitamin E (o, 15 mg, 180 mg and 250 mg vitamin E /kg of diet) from day old to day 42 of age. The quail are vaccinated intraoculary on day 10 and boosted on day 22 by Newcastle disease vaccine. Serum sample were collected on day 10, 14, 21, 28, 35 and 42. Growth performance, feed efficiency and antibody production against Newcastle disease vaccination were determined. The vitamin on the quail diet (250 mg/kg of diet) enhance growth performance and feed efficiency of quail. The vitamin E (180 mg, 250 mg/kg of diet) enhance humoral immune response in term of antibody production.